Environmental surveillance of the health risk of PM2.5-bound metals and metalloids in Wuxi, China, from 2020 to 2023 - Chen, Lijun; Zhang, Xuhui; Zhou, Xiaoxin; Gong, Yan; Kong, Lingcan; Wu, Yukang; Liu, Wenwei; Zhu, Pengfei (Frontiers in Public Health, 2025)
PM2.5 has been a major public concern due to its association with various diseases; however, its contamination is still not well controlled. From 2020 to 2023, the pollution characteristics of PM2.5-bound metals and metalloids were monitored in Wuxi, China. The surveillance targeted 26 components, including antimony (Sb), aluminum (Al), arsenic (As), beryllium (Be), cadmium (Cd), chromium (Cr), mercury (Hg), lead (Pb), manganese (Mn), nickel (Ni), selenium (Se), thallium (Tl), barium (Ba), cobalt (Co), copper (Cu), iron (Fe), molybdenum (Mo), silver (Ag), thorium (Th), vanadium (V), zinc (Zn), strontium (Sr), tin (Sn), lithium (Li), uranium (U), and rubidium (Rb). During the study period, The PM2.5 mass concentration ranged from 5.00 to 166.0 μg/m3, and the annual average PM2.5 concentration was 40.4 ± 26.1 μg/m3. The total concentration of 22 elements was 659.7 ± 318.5 ng/m3. Fe, Al, Zn, Mn, Pb, Cu, and Ba were seven dominant metals in PM2.5 accounted for 95.7% of the total metal concentrations (TMs). Both PM2.5 and most PM2.5-bound metals and metalloids exhibited decreasing trends to varying degrees and seasonal characteristics, peaking in winter. The result of enrichment factor (EF) suggested most elements mainly derived from anthropogenic pollution, while industrial emissions (32.4%), automotive emissions (27.9%), fuel combustion (26.2%) and dust emissions (13.5%) identified as the main sources by the positive matrix factorization (PMF). The hazard quotients (HQs) of all the metals were below 1, with Mn exhibiting highest HQ at 6.29 × 10−1 ± 3.28 × 10−1. The carcinogenic risks of five elements were as follows: Cd (5.21 × 10−7 ± 4.02 × 10−7), As (7.00 × 10−6 ± 3.83 × 10−6), Pb (1.24 × 10−7 ± 7.79 × 10−8), Ni (3.21 × 10−7 ± 1.62 × 10−7) and Cr (VI) (2.76 × 10−6 ± 1.31 × 10−6). These results indicate that both the non-carcinogenic and carcinogenic risks of individual elements monitored were within an acceptable range. However, considerable attention should be given to the comprehensive exposure risk associated with long-term exposure to Mn, As and Cr (VI). This study updated air pollution data, analyzed pollution sources and characteristics and discussed the potential risks of PM2.5-bound metals and metalloids. It is of great significance to reduce PM2.5 emissions and formulate environmental protection policies to protect the health of local residents.